(untitled) (Світ фінансів, 2017)
Івасів Б. С. Історія виникнення та перспективи розвитку електронних грошей. Висвітлено еволюційний розвиток форм грошей та розкрито механізм їх трансформації у сучасні електронні гроші на основі розвитку інформаційних технологій. Розглянуто теоретичні аспекти емісії та використання електронних грошей в економіці. Ivasiv B. History of Appearing and Perspectives of Electronic Money Development. The evolutional development of money forms is depicted, the mechanism of their transformation into modern electronic money on the basis of informational technologies development is carried out. The theoretical aspects of electronic money emission and its usage in economy are described.